2018
DOI: 10.3389/fpsyt.2018.00693
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Correlates of Resilience to Traumatic Events—A Comprehensive Review

Abstract: Improved understanding of the neurobiological correlates of resilience would be an important step toward recognizing individuals at risk of developing post-traumatic stress disorder (PTSD) or other trauma-related diseases, enabling both preventative measures and individually tailored therapeutic approaches. Studies on vulnerability factors allow drawing conclusions on resilience. Structural changes of cortical and subcortical structures, as well as alterations in functional connectivity and functional activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 77 publications
9
65
1
2
Order By: Relevance
“…Two recent reviews of the neuroimaging literature suggest that resilient functioning in those with a history of CM (i.e. the absence of any mental health disorder as an outcome [44] or the absence of post-traumatic stress disorder [45]) has largely been examined only cross-sectionally and is related to altered volumes and/or function of (midline) PFC as well as to limbic regions and their functional connectivity [45][46][47]. For instance, in the multisite IMAGEN study (n = 1870 adolescents), larger right middle superior PFC volumes were shown to be associated with resilient functioning on multiple domains of functioning, including academic achievement, conduct, relationships and emotional health [48].…”
Section: The Complex Interrelations Of Social Cognitive and Neurobiomentioning
confidence: 99%
“…Two recent reviews of the neuroimaging literature suggest that resilient functioning in those with a history of CM (i.e. the absence of any mental health disorder as an outcome [44] or the absence of post-traumatic stress disorder [45]) has largely been examined only cross-sectionally and is related to altered volumes and/or function of (midline) PFC as well as to limbic regions and their functional connectivity [45][46][47]. For instance, in the multisite IMAGEN study (n = 1870 adolescents), larger right middle superior PFC volumes were shown to be associated with resilient functioning on multiple domains of functioning, including academic achievement, conduct, relationships and emotional health [48].…”
Section: The Complex Interrelations Of Social Cognitive and Neurobiomentioning
confidence: 99%
“…To note that our classifier didn't identify several structural abnormalities found in previous cross-sectional studies of PTSD 7,25,34,38 . This includes the most replicated finding of small hippocampus 70 , but also abnormal volume of the amygdala, insular cortex, medial and dorsal prefrontal cortices (mPFC and dlPFC respectively) 28,31,33,[71][72][73] .…”
Section: Potential Biomarkers For Ptsdmentioning
confidence: 82%
“…Another structural feature found to be of importance to the classification was the volume of the rostral anterior cingulate cortex (rACC), such that lower rACC volume was associated with higher PTSD severity. Indeed, rACC volume was previously associated with PTSD 34,67,68 . Importantly, it was also shown to predict cognitive behavioral treatment response for individuals with PTSD 69 , suggesting its potential as a guiding mechanism-based early intervention closely after trauma.…”
Section: Potential Biomarkers For Ptsdmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, trauma exposure even in the absence of PTSD was shown to be associated with hippocampal volume decrease (17), and further hippocampal volume reduction was seen in chronic PTSD (18). Thus, it is yet to be clearly established whether reduced hippocampal size in PTSD is the result of trauma exposure, represents a risk factor for PTSD, or a combination of both (18,20,21). One possibility is that the hippocampus is not an isolated structural risk factor for PTSD, but that its pathological impact depends on the presence of additional brain anomaly.…”
Section: Introductionmentioning
confidence: 99%